2001
DOI: 10.1034/j.1399-3054.2001.1120413.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol oxidase and herbivore defense in trembling aspen (Populus tremuloides): cDNA cloning, expression, and potential substrates

Abstract: The biochemical anti-herbivore defense of trembling aspen (Populus tremuloides Michx.) was investigated in a molecular analysis of polyphenol oxidase (PPO; EC 1.10.3.2). A PPO cDNA was isolated from a trembling aspen wounded leaf cDNA library and its nucleotide sequence determined. Southern analysis indicated the presence of two PPO genes in the trembling aspen genome. Expression of PPO was found to be induced after herbivory by forest tent caterpillar, by wounding, and by methyl jasmonate treatment. Wound ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 31 publications
3
55
0
2
Order By: Relevance
“…Degradation of stilbenes may benefit bark beetles by improving the quality of substrate available for feeding their larvae, since the stilbenes remaining in the bark could be toxic. For example, the catechol groups present in the astringin core structure may be spontaneously or enzymatically rearranged to form reactive quinones (Haruta et al, 2001;Lin et al, 2010) under the semialkaline conditions prevailing in beetle guts (Balogun, 1969). These quinones can then alkylate reactive nucleophiles such as sulfhydryl and amino groups in proteins or amino acids (Felton et al, 1992;Son et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Degradation of stilbenes may benefit bark beetles by improving the quality of substrate available for feeding their larvae, since the stilbenes remaining in the bark could be toxic. For example, the catechol groups present in the astringin core structure may be spontaneously or enzymatically rearranged to form reactive quinones (Haruta et al, 2001;Lin et al, 2010) under the semialkaline conditions prevailing in beetle guts (Balogun, 1969). These quinones can then alkylate reactive nucleophiles such as sulfhydryl and amino groups in proteins or amino acids (Felton et al, 1992;Son et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that neither galled nor control chestnut oak tissues contained PPO, although we have measured vigorous PPO activity in tissues from other plant species under the same analytical conditions. Although PPO is present in a number of plants (Richard-Forget and Gauillard, 1997;Shin et al, 1997;Halder et al, 1998) and could reinforce some anti-herbivore functions of POX (Felton et al, 1994;Haruta et al, 2001), it may be absent (Grisebach, 1981) or difficult to extract from some plant tissues (Hsu et al, 1988;Burton and Kirchmann, 1997). We have found previously that PPO activity is low or absent in the leaves of chestnut oak (H. M. Appel and J. C. Schultz, unpublished data), and conclude that this enzyme either is not present in chestnut oak tissue, is present in an inactive form, or is not detectable using the methods employed.…”
Section: Discussionmentioning
confidence: 99%
“…The high DNA sequence similarity between poplars and aspens (Constabel et al, 2000;Haruta et al, 2001b) allowed us to make use of the aspen EST clone, identified as highly homologous to the RALF peptide, to design PCR primers. Using a poplar cDNA Table I…”
Section: Cloning and Characterization Of Ralf Cdnas From Poplarmentioning
confidence: 99%